The Success and Failure of the Schwann Cell Response to Nerve Injury - Jessen, Kristjan R.; Mirsky, Rhona (Frontiers in cellular neuroscience, 2019)
The remarkable plasticity of Schwann cells allows them to adopt the Remak (non-myelin) and myelin phenotypes, which are specialized to meet the needs of small and large diameter axons, and differ markedly from each other. It also enables Schwann cells initially to mount a strikingly adaptive response to nerve injury and to promote regeneration by converting to a repair-promoting phenotype. These repair cells activate a sequence of supportive functions that engineer myelin clearance, prevent neuronal death, and help axon growth and guidance. Eventually, this response runs out of steam, however, because in the long run the phenotype of repair cells is unstable and their survival is compromised. The re-programming of Remak and myelin cells to repair cells, together with the injury-induced switch of peripheral neurons to a growth mode, gives peripheral nerves their strong regenerative potential. But it remains a challenge to harness this potential and devise effective treatments that maintain the initial repair capacity of peripheral nerves for the extended periods typically required for nerve repair in humans.